Use of Indonesian Language in Space Outside Media in City of Timika - Novaria Panggabean (RETORIKA: Jurnal Ilmu Bahasa, 2020)
The strategic position of the Indonesian language for the Indonesian people is reflected in the third pledge of the Youth Pledge in 1928 which reads "We sons of Indonesia uphold the united language of Indonesian" and the 1945 Constitution Article 36 which states that "the language of the country is Indonesian". The aim of the study was to describe the use of Indonesian in outdoor media in the City of Timika. This study is focused on spelling mistakes, misuse of word choices, and sentence errors. The method used in this study is descriptive qualitative method and prescriptive technique, namely by describing and explaining the findings in the field and providing solutions to the problems found in the use of Indonesian in public spaces in Timika City. The results of this study showed that the forms of errors found in the use of Indonesian in the public area are spelling error, punctuation error, and writing error in absorption elements. The form of spelling errors consists of the use of letters, use of diphthong letters, use of capital letters, consonant combined letter, use of words, basic word, the word affix, reshape, word combination, preposition, abbreviations and acronyms. Meanwhile, the form of punctuation error consists of dot, commas, colon, hyphen, dash, exclamation mark, quotation mark, brackets, and italic line. Furthermore, the form of writing error in absorption elements consists of the use of sentences and words choice. In conclusion, there are still some errors found in public spaces in Timika city.